A Narrative Review on Dynamic Aspects of Remission in Type 2 Diabetes Mellitus along with Nutritional approaches - Nidhi Singh; Debasis Basu; Soutri Ghosh (The Bioscan, 2024)
Diabetes is becoming more widely acknowledged as a serious worldwide health epidemic and is considered to be chronic and progressive. Diabetes-related complications are a substantial cause of morbidity and mortality. The long-term effects of diabetes include microvascular diseases like nephropathy, neuropathy, and retinopathy as well as macrovascular complications like stroke, cardiovascular disease, and peripheral artery disease. With a lifelong commitment to monitoring and treatment, the traditional treatment strategy has been one of regulating glycemia and related cardiovascular disease risks. Only in the last decade have terms like "remission," "reversal," and even "cure" been mentioned in relation to the management of type 2 diabetes (T2DM), typically in the context of dramatic blood glucose improvements brought on by metabolic and bariatric surgery, aggressive medical weight loss methods, or carbohydrate restriction (with corresponding weight loss). Over the past few years, the idea of T2DM remission and the return of diabetes markers to normal levels has gained popularity. Various international guidelines are starting to recognize T2DM remission progressively. The development of evidence-based dietary recommendations has advanced, although there is still disagreement and uncertainty among the health professionals. This narrative review discusses through much detail about the various theories of diabetes remission as well as the methods that can be used to achieve T2DM remission, including dietary and lifestyle changes, exercise, bariatric surgery, and medicinal nutrition therapy. Although the idea of T2DM remission has become a practical possibility, it may not be possible to put it into routine clinical practice until long-term research establish the effectiveness of various techniques in this area.